Respuesta de la soja (Glicine max L. Merr) a enmiendas básicas en suelos de las provincias de Buenos Aires y Santa Fe - Vázquez, Mabel Elena (2012)
Soybean (Glicine max L. Merr) is a widespread crop in the Pampas region of Argentina and it is characterized by its high requirement of basic nutrients. Due to the acidification of some soils of this region, four field experiments were carried out in soils of moderate to high actual pH. The objectives of this study were to evaluate the effects of different rates and combination of amendments on soybean yield and yield components, as well as on soil chemical properties. The experimental design was in randomized complete blocks with a factorial arrangement. Treatments included rates between 0 and 2000 kg ha-1 of calcite/shells and dolomite, with and without gypsum addition (200 kg ha-1). The variables evaluated were yield, number of grains/plant, 1.000 kernel weight and soil chemical variables (actual and potential pH, CEC and exchange cations, organic C and N, extractable P). The addition of basic amendments produced crop responses between 209,2 and 1.264 kg ha-1; these responses were negatively related to pH and Ca, and showed a positive correlation with the production level. Crop yield responses could not be explained by the effect of only a few of its components. The changes that occurred in the edaphic properties were not related to the yield increase. Dolomite additions tended to produce greater crop responses, as well as the highest rates of both amendments. In P-deficient soils, a synergistic effect was observed when combining the amendment with P fertilizer.